Cell-Based Assays in Practice: Cell Markers from Autofluorescent Proteins of the GFP-Family - Wolff, Michael; Kredel, Simone; Wiedenmann, Jorg; Nienhaus, G. U.; Heilker, Ralf (Combinatorial Chemistry & High Throughput Screening, 2008)
The more recently discovered anthozoan fluorescent proteins (FPs) and the classic Aequorea victoria Green Fluorescent Protein (avGFP) as well as their derivatives have become versatile tools as live cell markers in fluorescence microscopy. In this review, we show the use of these FPs in drug discovery assays. Assay examples are given for the application of FPs in multiplexed imaging, as photosensitizers, as fluorescent timers, as pulse-chase labels and for robotically integrated compound testing. The development of fast microscopic imaging devices has enabled the application of automated fluorescence microscopy combined with image analysis to pharmaceutical high throughput drug discovery assays, generally referred to as High Content Screening (HCS).
Keywords: anthozoan